Mutmainnah Personality in the Qur'an as a Form of Aristotle's Eudaimonia Ethics - Muhammad Yuchbibun Nury; Dhur Anni; Slamet Arif; Habibatun Nuriyyah; Diki Muhammad Roofid (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Personality is one of the most complex and dynamic aspects of a human being. It plays a crucial role in determining how individuals interact with their environment, face life’s challenges, and achieve their goals. Understanding personality is essential for improving quality of life and attaining happiness. For classical philosophers such as Aristotle, happiness represents the highest level a person can achieve. The sciences he developed aimed to attain inner peace, or eudaimonic happiness. This form of happiness can be achieved through a good nature, a peaceful heart, and a healthy body. This study employs a qualitative method with a library research approach to analyze the term mutmainnah in the Qur'an. The results indicate that the verses containing the word mutmainnah can be interpreted as guidelines for shaping personality. Furthermore, eudaimonic happiness, achieved through mutmainnah personality begins with using worldly enjoyment as a means to apply spiritual values, while prioritizing the enjoyment of the hereafter as the ultimate goal of human life. Thus, mutmainnah as a personality trait reflects the wisdom of positive qualities that promote human self-development and help prevent mental health disorders